The Necessity of Systemic Ultrasound Examination for Neonate within One Week in Taiwan: Two Cases Reports - Chang, Yu-Chen; Hung, Ching-Yi; Lee, Chien-Hsing (International Journal of Child Health and Nutrition, 2025)
Many congenital abdominal anomalies and tumors are asymptomatic and easily miss early detection. Ultrasound examinations, non-invasive and safe, play a crucial role in diagnosing congenital abnormalities. We advocate neonatal ultrasound screening programs encompassing multiple systems, aiding early disease diagnosis and prompt intervention. This article reported two cases that missed prenatal examination and found abnormalities through a ultrasound program within one week after birth.